2021
DOI: 10.4081/ripppo.2021.537
|View full text |Cite
|
Sign up to set email alerts
|

Dreaming in quarantine: linguistic analysis of referential process of dreams during COVID-19 pandemic lockdown

Abstract: The spread of coronavirus disease 2019 (COVID-19) became a collective trauma adversely affecting physical and psychological health. The impact of this trauma made itself manifest in a myriad of ways, including through dreams. This study aimed to explore the Referential Process (RP, Bucci, 2021) of dreams reported during quarantine. Dream samples were collected through a social blog. Linguistic analysis and clinical evaluation were conducted to explore the group’s collective elaboration of a shared traumatic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(42 reference statements)
3
8
0
Order By: Relevance
“…Concerning the emotional tone of participants’ dreams, our results confirmed our fourth hypothesis. In line with other COVID-19 studies (Borghi et al, 2021; Gorgoni et al, 2021; Mariani et al, 2021; Schredl & Bulkeley, 2020), we found a higher proportion of negative dream emotions relative to positive dream emotions. Fear/fright/terror and anxiety/anguish/worry were the most frequent emotions in the dream reports, representing approximately 50% of the dreams.…”
Section: Discussionsupporting
confidence: 93%
“…Concerning the emotional tone of participants’ dreams, our results confirmed our fourth hypothesis. In line with other COVID-19 studies (Borghi et al, 2021; Gorgoni et al, 2021; Mariani et al, 2021; Schredl & Bulkeley, 2020), we found a higher proportion of negative dream emotions relative to positive dream emotions. Fear/fright/terror and anxiety/anguish/worry were the most frequent emotions in the dream reports, representing approximately 50% of the dreams.…”
Section: Discussionsupporting
confidence: 93%
“…Further research should be carried out to confirm these findings in a more generalized way, concluding that dreams allow for a facilitation in the elaboration of traumatic emotional experiences. Our results support the findings of researchers who found that dreams could play a role in the reorganization of experience, particularly, in reference to memories, trauma, and the general ability of problem solving ( Fosshage, 2007 ; Mariani et al, 2021 ). These results are in line with the studies on the psychotherapeutic process, which highlight how dream processing allows for the processing of traumatic experiences ( Gennaro et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Two studies from Mariani and co-workers (2021a; 2021b) also focused on dream themes. In the first study ( Mariani et al, 2021a ), the authors collected dreams from an online blog during the lockdown and analysed dream themes using different computerized referential processes linguistic measures, revealing three dream clusters: symbolizing process, arousal of emotional activation, reflection/reorganizing elaboration. In the second study ( Mariani et al, 2021b ), they applied computerized referential process linguistic measures and Affect Salience Index, a measure of arousal in written texts ( Fornari, 1976 , Salvatore and Freda, 2011 , Valsiner, 2021 ), on dreams and waking thoughts collected during the lockdown.…”
Section: Resultsmentioning
confidence: 99%